2021
DOI: 10.18280/ijdne.160201
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Efficiency of a Solar Water Heater Construction from Recycled Plastic Bottles

Abstract: A solar polymer heat exchanger is designed to heat water; its primary materials are plastic water bottles with a capacity of 1.5 liters. These materials were recycled to preserve the environment and to make use of it again. The thermal insulation properties are adopted for the characterization of polymeric materials. These properties concern the conservation of energy for the longest period of time and the absence of problems caused by rust and corrosion, which are usually encountered in traditional heat excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Abu-Mulaweh et al [5] et al explained designing and development of solar water heating system experimental apparatus. Besma Chekchek et al [6] constructed solar water heater from plastic bottles and evaluate its thermal performance. Sivakumar et al [7] explored the effect of zig-zag arrangement of riser tubes from the existing collector as well as the number of riser tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Abu-Mulaweh et al [5] et al explained designing and development of solar water heating system experimental apparatus. Besma Chekchek et al [6] constructed solar water heater from plastic bottles and evaluate its thermal performance. Sivakumar et al [7] explored the effect of zig-zag arrangement of riser tubes from the existing collector as well as the number of riser tubes.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the optimized oval-tube outperforms the conventional circular-tube shape by approximately 13% and 15% in heat transfer rates, 9% and 13.5% in coefficients of performance (COP), and 13% and 16.6% in heat transfer coefficients for Re = 1030 and 2060, respectively. Moreover, other investigations by numerical and experimental treatments have been carried out by Sakhri et al [42][43][44], Chamkha et al [45], Boursas et al [46], Chekchek et al [47], Hadidi et al [48], Menni et al [49][50][51][52], Ahmad et al [53], Salmi et al [54], Ameur et al [55], Mahammedi et al [56], Maouedj et al [57], etc. Their studies suggested different models of heat exchangers in order to improve the performance under various limit conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The biggest improvement in the turbulence magnitude was reached in the area within a distance of two heights of the VG from the lower wall just downstream of the VG. Other related achievements are available in the literature like Sakhri et al [18][19][20], Chamkha and Menni [21], Boursas et al [22], Chekchek et al [23], Hadidi et al [24], and Menni et al [25]. Also, Salmi et al [26] tried to enhance the convective heat transfer in CHE baffles with vortex generators.…”
Section: Introductionmentioning
confidence: 99%